2000
DOI: 10.4049/jimmunol.164.12.6147
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Proteasome Inhibitors Lactacystin and Epoxomicin Can Be Used to Either Up- or Down-Regulate Antigen Presentation at Nontoxic Doses

Abstract: The complete inhibition of proteasome activities interferes with the production of most MHC class I peptide ligands as well as with cellular proliferation and survival. In this study we have investigated how partial and selective inhibition of the chymotrypsin-like activity of the proteasome by the proteasome inhibitors lactacystin or epoxomicin would affect Ag presentation. At 0.5–1 μM lactacystin, the presentation of the lymphocytic choriomeningitis virus-derived epitopes NP118 and GP33 and the mouse CMV epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 54 publications
9
77
0
Order By: Relevance
“…The lacZ-based color reaction was performed and measured, as detailed elsewhere (27). In case of vaccinia-infected stimulator cells, supernatants of cocultures from T cell hybridomas and stimulators were collected 24 h postinfection and analyzed by IL-2 ELISA (BD Pharmingen).…”
Section: Lacz Assaymentioning
confidence: 99%
“…The lacZ-based color reaction was performed and measured, as detailed elsewhere (27). In case of vaccinia-infected stimulator cells, supernatants of cocultures from T cell hybridomas and stimulators were collected 24 h postinfection and analyzed by IL-2 ELISA (BD Pharmingen).…”
Section: Lacz Assaymentioning
confidence: 99%
“…Epoxomicin (Sigma) blocks the proteasomal machinery irreversibly by inhibiting primarily chymotrypsin-like, but also trypsin-like, and peptidylglutamyl peptide-hydrolyzing activities of the proteasome [48]. Thus, it interferes with production of proteasome-dependent MHC-I ligands [49]. …”
mentioning
confidence: 99%
“…These findings altogether indicated that the restoration of 2B2-CTL recognition by pretreatment with bortezomib especially in combination with IFN-g is not due to E6 mRNA up-regulation, but rather is likely caused by modulation of proteasomal function by bortezomib, as reported previously. [11][12][13] HLA-A*2402-restricted E6 49-57 -specific CD81 T cells can be induced from CIN and cervical cancer patients despite low precursor frequencies Identification of the immunogenic HLA-A*2402-restricted HPV-16 E6-derived epitope enabled us to synthesize the HLA-A24/E6 [49][50][51][52][53][54][55][56][57] tetramer, which clearly stained 2B2-CTL (Fig. 6a, right panel) and detected a growing population of E6 [49][50][51][52][53][54][55][56][57] -specific T cells in bulk culture after stimulation from which 2B2-CTL was generated (Fig.…”
Section: Treatment Of Cervical Cancer Cell Lines With Proteasome Inhimentioning
confidence: 99%
“…Since presentation of certain CTL epitopes of tumor and viral antigens is reported to be enhanced by treatment of target cells with proteasome inhibitors, [11][12][13] we first attempted to sensitize SiHa cells with epoxomicin or bortezomib. Epoxomicin is an irreversible proteasome inhibitor, which is about 100-fold more potent than lactacystin, 12 while bortezomib is a reversible proteasome inhibitor. 15 As shown in Figure 3a, treatment of SiHa cells with epoxomicin or bortezomib induced IFN-g production from 2B2-CTL but not from an irrelevant CTL clone or SiHa cells themselves.…”
Section: Treatment Of Cervical Cancer Cell Lines With Proteasome Inhimentioning
confidence: 99%
See 1 more Smart Citation